Component analysis of binary media using acoustic reflectoimpedancemetry - P. O. Lipovko; M. L. Loganchuk (Компьютерные исследования и моделирование, 2015)
A computer model of component analysis of binary media, based on application of a new method acoustic reflecto-impedancemetry and realized in graphic programming environment LabVIEW is considered. Prospects of metrological and instrumental provisions of experimental applications of the model are discussed.